Esterilização de cães com injeção intratesticular de solução à base de zinco. - Erika Christina Santos Oliveira (2006)
The aim of this study was to evaluate the efficacy of a single intratesticular injection of a zinc-based solution in causing sterility of male dogs. Fifteen mongrel dogs were randomized into 3 groups (5dogs/group). Group one, the control, was injected with saline solution. Group two, which consisted of animals ranging from 8 months to 1,5 years old and Group 3, animals ranging from 2 to 4 year old, were injected with a zinc-based solution, at six different doses (0.2 to 1.0mL), based on testicular width (10 to 27mm), determined by a caliper. No biting/licking was recorded after the injection in the treated animals. Transient testicular swelling was reported in the treated animals in the first three days after injection. Scrotal pain when the testis were manipulated was not observed in any animal of either group. By one month, the testicles in the treated animals decreased 8% in size (p<0.05). At 60 days post-injection, 8 of 10 of the treated animals were azoospermic. The two non azoospermic dogs (Group 3) were found to be oligospermic (<10x106 spermatozoa/ml). There were no significant differences between treated and control groups for the biochemical parameters and testosterone concentration. Histological examination of treated groups revealed degeneration and decreased number of germ cells, vacuolation of germ cells in atrophic seminiferous tubules. Leydig cells showed different degree of lipid degeneration and necrosis. The majority of the seminiferous tubules in all dogs were lined only by Sertoli cells, which were vacuolated. Ultrastructure of testis of treated groups showed degenerated Sertoli and Leydig cells characterized by numerous mitochondria with lack of a matrix and agglomeration of lysosomal bodies. Elongated spermatids cytoplasm was characterized by tubules of hyperplasied and hypertrophied smooth endoplasmic reticulum and numerous Golgi apparati. Round spermatids in Golgi phase showed lyses of acrosomal vesicle. The results indicated that intratesticular injection of zinc-based solution was effective in impair spermatogenesis of dogs of different ages.